Uncovering Leishmania–macrophage interplay using imaging flow cytometry - Terrazas, Cesar (J Immunol Methods, 2015)
Host–pathogen interaction is an area of considerable interest. Intracellular parasites such as Leishmania reside inside phagocytes such as macrophages, dendritic cells and neutrophils. Macrophages can be activated by cytokines such as IFN-γ and Toll like receptor (TLR) agonists resulting in enhanced microbicidal activity. Leishmania parasites hijack the microbicidal function of macrophages, mainly by interfering with intracellular signaling initiated by IFN-γ and TLR ligands. Here we used transgenic Leishmania donovani parasites expressing the red fluorescent protein DsRed2 and imaging-flow cytometry technology to evaluate parasitic loads inside the macrophage in vitro. Further, this methodology enables us to visualize impairment in NFκB translocation to the nucleus in L. donovani infected macrophages. Additionally we show that uninfected bystander macrophages have a similar impairment in NFκB translocation as in L. donovani infected macrophages in response to the TLR4 agonist LPS. This evidence suggests a possible immunosuppressive role for infected macrophages in regulating the activation of uninfected bystander macrophages.